Kajian Etnosains Membuat Jeruk Maman Sebagai Sumber Pembelajaran IPA - Azmi Asra; Jismi Mubarrak (JURNAL PENDIDIKAN ROKANIA, 2023)
The identity of local cultural ownership in Indonesia needs to be improved as a source of learning in science education. The development of the current 2013 curriculum in science education pays attention to local cultural wisdom (ethnoscience) national identity, character and local cultural customs. This study uses a descriptive descriptive approach that tries to observe and conduct a comprehensive study of the implementation of meaningful learning which can be done by associating science concepts with community activities around students, especially activities related to culture, customs of the surrounding community which are one of the one identity of the Indonesian nation.